Is the Future Bright or Bleak? Assessing Past and Future Outlooks Across the Adult Lifespan. (22nd September 2021) - Silaj, Katie M.; Schwartz, Shawn T.; Castel, Alan D.; McDonough, Ian M.
An individual's outlook on society can change over time and can be related to both their physical and mental health. Here, we developed an instrument to measure outlooks on the past and future in relation to the present in 413 adults ranging in age from 18 to 80 years. Exploratory and confirmatory factor analyses were conducted on independent samples and test–retest reliability was assessed in a subset of participants. Construct validity of the two past and future scales was assessed by relating them to 1) pre-existing scales measuring related constructs, and 2) beliefs and safety behaviors during the COVID-19 pandemic. The final Bright or Bleak Scale (BOBS) consists of a past and future scale, each with two factors measuring societal and personal outlooks. Brighter future societal and personal outlooks were positively associated with longer future time perspectives, while self-reporting a higher likelihood of already having contracted COVID-19 was related to bleaker past societal and personal outlooks.